Implementation of Customer Relationship Management (CRM) in Operational Management - Imam Wibowo (SEAN Institute, 2023)
CRM has become a critical element in modern business strategy, especially in maintaining positive relationships between companies and customers. This research tries to understand how the implementation of CRM can influence and improve the efficiency and effectiveness of an organization's operational management. This research aims to explore and analyze the implementation of Customer Relationship Management (CRM) in the context of operational management. The research results show that the implementation of Customer Relationship Management (CRM) in operational management has a positive impact on customer relationships and operational efficiency. Customer data analysis has enabled organizations to deliver more personalized services tailored to individual needs, while the integration of CRM systems with operational management improves the accessibility and manageability of customer data. Employee training and emphasis on consistent communication also contribute to strengthening relationships with customers. The use of relevant performance metrics and regular monitoring provides a clear picture of the impact of CRM implementation, while continuous improvement and development based on customer evaluation and feedback supports responsiveness to changing customer needs. Through a cycle of continuous improvement, organizations can continually improve their operations, create better customer experiences, and maintain a competitive advantage in a dynamic business environment.